For the Fourier transform of the convolution in and D' and Z' (JOURNAL OF ADVANCES IN MATHEMATICS, 2021)
In this paper, we give another proof of the known lemma considering the Fourier transform of the convolution of a distribution and a function. Also, we give its application in the mentioned spaces.